Identifikasi Resiko Cedera Otot Pada Postur Tubuh Operator Di Area Produksi Dengan Metode Rapid Upper Limb Assessment (RULA) - Hartono, Hartono; Hidayat, Dian Friana; Kustantyo, Andika (Journal Industrial Manufacturing, 2025)
The production process in the manufacturing industry still uses human resources in working, there are manual handling conditions that can cause fatigue in workers. A worker's fatigue can affect the worker's attitude, where workers move in an unergonomic manner, such as working with the wrong body posture. As in the production in the plastic cutting machine manufacturing industry where the operator's long work posture activities such as standing, squatting, bending and doing repetitive movements can cause fatigue, discomfort, and pain in the limbs so that it is necessary to analyze the work posture to reduce the risk of musculoskeletal disorders (MSDs) by using ergonomic analysis, namely the Rapid Upper Limb Assessment (RULA) method and the Nordic Body Map questionnaire. The results of the RULA assessment of operators showed a high level of risk, the assessment of grinding machine operators, lathe operators, milling machine operators, and welding operators showed action level 3, and the assessment of painting operators showed action level 4. Suggestions for improvement were made by changing the operator's body posture when working, such as grinding machine operators, milling machine operators, welding operators, and assembly operators obtaining action level 2 and the proposed body posture of lathe operators and painting operators obtaining action level 1.Keywords: Ergonomics, Posture, Musculoskeletal Disorders (MSDs), Rapid Upper Limb Assessment (RULA), Nordic Body Map